5G beam-steering 2×2 butler matrix with slotted waveguide antenna array - Noorlindawaty Md. Jizat; Nazihah Ahmad; Zubaida Yusoff; Nuramirah Mohd Nor; Mursyidul Idzam Sabran (Universitas Ahmad Dahlan, 2019)
In this research paper, substrate integrated waveguide (SIW) was proposed as a technique by realizing bilateral edge walls to produce a compact 5G beam-steering antenna at 24 GHz. The beam forming network is produced using SIW directional coupler perform as 2×2 Butler Matrix (BM) fed with SIW slotted waveguide antenna array. The output signal is steered from -29 degrees and +29 degrees when the signal is fed to the respective input ports. If one of the input ports is fed, the signal is evenly distributed between the adjacent output ports with 90 degree constant phase shift. The compact size of directional coupler was designed by longitude slots on the surface of SIW substrate with bandwith of 16.85% at the operating frequency. The proposed antenna produce gain of 6.34 dB at operating frequency and the promising outcome of the beam steering make proposed design suitable for 5G communications especially with tracking capabilities.